Hassan v United Kingdom: The Interaction of Human Rights Law and International Humanitarian Law with regard to the Deprivation of Liberty in Armed Conflicts - De Koker, Cedric (Utrecht Journal of International and European Law, 2015)
In Hassan v United Kingdom, the Grand Chamber of the European Court of Human Rights reviewed the deprivation of liberty of a young male by British armed forces during the phase of active hostilities in Iraq, which had raised issues relating to extraterritoriality, the right to liberty and security in times of armed conflict and the relationship between international humanitarian law (IHL) and human rights law (HRL).1 In its judgment of 16 September 2014, the Court ruled that by reason of the co-existence of the safeguards provided by IHL and by the European Convention on Human Rights (ECHR) in time of armed conflict, the grounds of permitted deprivation of liberty found in both bodies of law should, as far as possible, be accommodated and applied concomitantly. The greatest merit of the judgment is that for the first time it explicitly offered its view on the interaction between IHL and HRL and did not rely on the lex specialis principle, the traditional but flawed method for explaining the relationship between these spheres of law. However, the judgment is also a missed opportunity as the Court limited its analysis to the case at hand and provided limited guidance for the future, leaving a number of questions unaddressed.